Encapsulation of essential oils in chitosan nanoparticle formulations and Investigation on their antioxidant and antibacterial properties. - Shetta, Amro Abdel Azeem (AUC Knowledge Fountain, 2017)
Peppermint oil (PO) and Green Tea oil (GTO) are two essential oils (EOs) were encapsulated in chitosan nanoparticles (CS NPs) via two-steps method (emulsification followed by ionic gelation). Encapsulation of GTO and PO in CS NPs were investigated through different characterization techniques such as; Fourier transform infrared (FT-IR) spectroscopy, powder X-ray diffraction (XRD). Both NPs (CS/PO NPs and CS/GTO NPs) showed a spherical shape with 20-90 nm size range as detected by Transmission electron microscopy (TEM). Thermogravimetric analysis (TGA) was used to study the thermal stability of both bulk and encapsulated EOs that showed an enhancement in the thermal stability of both encapsulated EOs by about 2.18 and 1.75 folds for PO and GTO, respectively. Through UV-vis spectroscopy, both encapsulation efficiency (EE%), loading capacity (LC%) and in-vitro release were estimated. EE% of CS/PO NPs and CS/GTO NPs were about 82-78% and 22-81%, respectively, when the initial EO amount was 0.25–1 w/w CS. Whereas, the loading capacity (LC%) of CS/PO NPs and CS/GTO NPs were about 8-22% and 2.2-23%, respectively for the initial EO amount was 0.25–1 w/w CS. The in-vitro release studies of both EOs showed an initial rapid release profile followed by a slow release at two different pH conditions: acidic pH (acetate buffer) and neutral pH (phosphate buffer saline). Furthermore, the stability of the total phenolic contents (TPC) of both EOs in CS NPs was studied using Folin–Ciocalteu reagent. The antioxidant activity of both pure and encapsulated PO and GTO was evaluated by 2,2-diphenyl-1-picrylhydrazyl radical (DPPH). The antioxidant activities of CS/PO NPs and CS/GTO NPs were improved by about 2 and 2.4 folds, respectively. Finally, agar dilution and colony counting method were used to study the antibacterial activity of pure and encapsulated PO and GTO against Gram positive (Staphylococcus aureus) and Gram negative (Escherichia coli) bacteria. In case of Gram positive bacteria, encapsulated PO showed an enhanced antibacterial activity by about 39.63%, while encapsulated GTO showed an improvement in antibacterial activity by about 57.5% on the other hand, against Gram negative bacteria, encapsulated PO showed an enhanced antibacterial activity by about 3%, while encapsulated GTO showed an improvement in antibacterial activity by about 1.8%.